Macrofaunal Communities Associated with Ecklonia radiata Holdfast Along the Southeast Coast of South Africa - Naledi Nkohla; Thembinkosi Steven Dlaza (Diversity)
Kelp forests are recognized as biodiversity hotspots and ecosystem engineers, while the macroinvertebrates linked with their holdfasts serve as markers of pollution and ecological and environmental change. Notwithstanding the evident ecological and economic importance of this system, no research has been undertaken in South Africa to examine the macroinvertebrate community assemblage patterns within the Ecklonia radiata holdfast, nor the mechanisms driving the observed distribution patterns. This study identified and compared the assemblage patterns of holdfast-associated macroinvertebrates across several sites using univariate and multivariate approaches, and delineated physical factors influencing invertebrate community organization. The key findings indicated that abundance exhibited little variations among sites, with Dwesa presenting the highest average abundance and Kob-Inn the lowest. Mazeppa exhibited the greatest species richness, succeeded by Dwesa and Nqabara. Beta diversity measured 0.42, with turnover and nestedness contributing equally. Xhorha and Nqabara exhibited the largest local contribution to beta diversity (LCBD) regarding turnover, whereas Mazeppa and Kob-Inn demonstrated the highest LCBD in terms of nestedness. Substantial clustering among sites was observed, with each site harbouring a distinct assemblage of macroinvertebrates. Species that discriminated the sites were Zeuxoides helleri, Cirolana venusticauda and Amphipholis squamata.